Crystal structure of bis{3-(3,4-dimethylphenyl)-5-[6-(1H-pyrazol-1-yl)pyridin-2-yl]-4H-1,2,4-triazol-4-ido}iron(II) methanol disolvate - Kateryna Znovjyak; Igor O. Fritsky; Tatiana Y. Sliva; Vladimir M. Amirkhanov; Sergey O. Malinkin; Sergiu Shova; Maksym Seredyuk (Acta Crystallographica Section E: Crystallographic Communications, 2022)
As a result of the high symmetry of the Aea2 structure, the asymmetric unit of the title compound, [FeII(C18H15N6)2]·2MeOH, consists of half of a charge-neutral complex molecule and a discrete methanol molecule. The planar anionic tridentate ligand 2-[5-(3,4-dimethylphenyl)-4H-1,2,4-triazol-3-ato]-6-(1H-pyrazol-1-yl)pyridine coordinates the FeII ion meridionally through the N atoms of the pyrazole, pyridine and triazole groups, forming a pseudo-octahedral coordination sphere of the central ion. The average Fe—N bond distance is 1.955 Å, indicating a low-spin state of the FeII ion. Neighbouring cone-shaped molecules, nested into each other, are linked through double weak C—H(pz)...π(ph') interactions into mono-periodic columns, which are further linked through weak C—H...N′/C′ interactions into di-periodic layers. No interactions shorter than the sum of the van der Waals radii of the neighbouring layers are observed. Energy framework analysis at the B3LYP/6–31 G(d,p) theory level, performed to quantify the intermolecular interaction energies, reproduces the weak interlayer interactions in contrast to the strong interaction within the layers. Intermolecular contacts were quantified using Hirshfeld surface analysis and two-dimensional fingerprint plots, showing the relative contributions of the contacts to the crystal packing to be H...H 48.5%, H...C/C...H 28.9%, H...N/N...H 16.2% and C...C 2.4%.